PANCASILA SEBAGAI FILTER SOSIAL DI TENGAH ERA DIGITAL - Wau, Jemima Jasmine Graciana (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
The digital era has brought about major transformations in various aspects of social, economic and cultural life. Although it provides several conveniences, this era also provides challenges in the form of the spread of hoaxes, social media addiction, and a decline in moral values, especially among the younger generation. This essay aims to examine how Pancasila can act as a social filter in dealing with the negative impacts of the digital era. The noble values in Pancasila are able to become an ethical foundation that guides people's behavior in real and virtual life.